Anaerobic Cometabolic Conversion of Benzothiophene by a Sulfate-Reducing Enrichment Culture and in a Tar-Oil-Contaminated Aquifer - Annweiler, Eva (American Society for Microbiology, 2001)
Anaerobic cometabolic conversion of benzothiophene was studied with a sulfate-reducing enrichment culture growing with naphthalene as the sole source of carbon and energy. The sulfate-reducing bacteria were not able to grow with benzothiophene as the primary substrate. Metabolite analysis was performed with culture supernatants obtained by cometabolization experiments and revealed the formation of three isomeric carboxybenzothiophenes. Two isomers were identified as 2-carboxybenzothiophene and 5-carboxybenzothiophene. In some experiments, further reduced dihydrocarboxybenzothiophene was identified. No other products of benzothiophene degradation could be determined. In isotope-labeling experiments with a [(13)C]bicarbonate-buffered culture medium, carboxybenzothiophenes which were significantly enriched in the (13)C content of the carboxyl group were formed, indicating the addition of a C(1) unit from bicarbonate to benzothiophene as the initial activation reaction. This finding was consistent with the results of earlier studies on anaerobic naphthalene degradation with the same culture, and we therefore propose that benzothiophene was cometabolically converted by the same enzyme system. Groundwater analyses of the tar-oil-contaminated aquifer from which the naphthalene-degrading enrichment culture was isolated exhibited the same carboxybenzothiophene isomers as the culture supernatants. In addition, the benzothiophene degradation products, in particular, dihydrocarboxybenzothiophene, were significantly enriched in the contaminated groundwater to concentrations almost the same as those of the parent compound, benzothiophene. The identification of identical metabolites of benzothiophene conversion in the sulfate-reducing enrichment culture and in the contaminated aquifer indicated that the same enzymatic reactions were responsible for the conversion of benzothiophene in situ.